Actualization Of The Forms Of Patriotism In Indonesia - Kamrussamad, Muhamad Ali Embi (International Journal of Advanced Science and Technology, 2020)
In the era of globalization, the spirit of patriotism has become increasingly important to be explored and practiced. This is because the Indonesian state is inhabited by people who are different in terms of religion, ethnicity and ideology. If every Indonesian met, understood ethnicity, political ideology, or a higher and foremost party from the Indonesian state itself, then surely the Indonesian state would not be able to achieve development and improvement. In this diverse Indonesian society, important patriotism among its people is important. Through high patriotism, it will only be able to deter individuals in Indonesian society before choosing prejudists and radicals against any religion, ethnicity, ideology or even those who do not join them. This prevailing phenomenon has raised the question of whether people really consider the purpose of patriotism? or is patriotism understood in a narrow form? That is, the community is only required to fight to take up arms in the compilation state against the enemy when in a safe environment the community does not need to care about the state of the country. It may also be that the public is mistaken with the concept of patriotism with the agreement that patriotism only applies in symbolic form, whereas the community agrees to state symbols such as leaders, flags or national anthem associations which are communicated by the state that have been successfully declared. The important question that addresses the spirit of patriotism is very interesting to study. Especially in Indonesian society which consists of various layers of society. Through this study we will be able to discuss patriotism as well as the forms of patriotism that Indonesian society has today based on demographics.